Does the Internet Reduce Gender Gaps? : The Case of Jordan - Viollaz, Mariana (2021)
This article investigates the link between digital technologies and female labor market outcomes in a country with one of the largest gender disparities. It exploits the massive roll-out of mobile broadband technology in Jordan between 2010 and 2016 to identify the effect of internet adoption on labor force participation. Using panel data at the individual level with rich information on labor market outcomes, internet use and gender-biased social norms, the article finds that internet adoption increases female labor force participation but has no effect on male labor force participation. The increase in online job search explains some -- but not all -- of the total increase in female labor force participation. Only older and skilled women experience an increase in employment in response to having internet access. The internet also reduces the prevalence of gender-biased social norms, early marriage and fertility.